THU0287 The prevalence of remission in a real-life cohort of psoriatic arthritis patients treated with synthetic or biologic disease modifying drugs. (12th June 2018) - Favalli, E.G.; Fassio, A.; Bugatti, S.; Batticciotto, A.; Quartuccio, L.; Filippini, M.; Parisi, S.; Biggioggero, M.; Zanframundo, G.; Giovannini, I.; Ditto, M.C.; Idolazzi, L.
Abstract : Background: The treat-to-target (T2T) strategy for the management of psoriatic arthritis (PsA) recently proposed by EULAR recommendations suggests to ideally achieve remission/Low Disease Activity (LDA) in all treated patients, but nowadays data on remission/LDA rate in a real-world setting are still lacking. Objectives: To evaluate the disease activity state in a real-life cohort of PsA patients treated with synthetic and/or biologic disease modifying drugs (DMARDs). Methods: We undertook a cross-sectional analysis of all PsA consecutive patients enrolled in a large Italian multicentric registry including 7 Italian tertiary rheumatology centres. Disease activity defined as number of swollen (SJ) and tender (TJ) joints, Leeds Enthesitis Index (LEI), number of dactylitis, Body Surface Area (BSA), patient global assessment (PGA), patient pain (PP), Health Assessment Questionnaire Disability Index (HAQ-DI), and C-reactive protein (CRP, mg/L) were computed and the rates of patients achieving Disease Activity in PSoriatic Arthritis (DAPSA) remission/LDA and Minimal Disease Activity (MDA) were calculated. Subanalysis after stratification according to ongoing treatment (sDMARDs or bDMARDs) were also performed. Results: The study population included 362 PsA patients (56.6% men; mean [±standard deviation, SD] age 53.3±12.4 years; mean [±SD] disease duration 9.4±8.2 years), treated with sDMARDs (15.8%, mainly methotrexate [66.6%]) or bDMARDs (79.6%, mainly anti-TNF agents [72.9%], as monotherapy [78.1%] or in combination with sDMARDs [21.9%]). Oligoarthritis (32%), polyarthritis (42%), axial involvement (11.9%), enthesitis (10.5%), and dactilytis (3.6%) were the reported predominant subsets of PsA. In the overall population the mean values [±SD] of disease activity measures were: SJ count 1.4±2.6, TJ count 1.9±3, LEI 0.5±1.1, number of dactylitis 0.1±0.3, BSA 2.6±6.9, PGA 1.4±2.6, PP 3±2.6, HAQ-DI 0.4±0.5, CRP level 3.4±8, and DAPSA 9.3±9.2. The rates of DAPSA LDA and remission were 46.9% and 31.7%, respectively. We found 51.6% of patients achieving MDA, without significant difference according to ongoing treatment (53.4% and 51% in bDMARD versus sDMARD treated patients, respectively; p=0.87). Conclusions: In our real-life cross-sectional analysis, an acceptable comprehensive disease control was reported only in half of patients, irrespectively of ongoing therapy. These findings suggest the need to further improve the real-world application of T2T strategy for the management of PsA. Disclosure of Interest: None declared